2019
DOI: 10.4236/ajps.2019.101014
|View full text |Cite
|
Sign up to set email alerts
|

Underutilized Edible Plants of Nagaland: A Survey and Documentation from Kohima, Phek and Tuensang District of Nagaland, India

Abstract: With the rapid rise in the population, there is higher demand of the food supply to fed millions of people. As such dependence on the few major staple crops to meet the needs of the people has led to increases in starvation and poverty. Underutilized edible plants offer a cheaper and affordable option in providing more crop diversification to tackle these problems and provide food security to the poor to the world in general and to the developing countries in particular. In the present investigation, a total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Wild edible fruits have also been proven to enhance household food security under normal conditions (Broegaard et al 2017), as well as during crop insufficiency (Erskine et al 2015) in both rural and urban areas (Clark and Nicholas 2013). Moreover, the wild edible fruit plants have multiple uses such as cosmetics (Gebauer et al 2016), medicine (Tshikalange et al 2016;Dreher 2018;Elfrida et al 2021;Majumder et al 2021;Navia et al 2021a;Suwardi et al 2021), spices or condiments (Navia et al 2020a), crafts (Atato et al 2012;Hazarika and Singh 2018), traditional ceremonies (Sutrisno et al 2020), fiber (Karun et al 2014), fuel (Debela et al 2012;Klimas et al 2012), and even as a substantial income for local communities, particularly those living in remote areas (Deb et al 2013;Suwardi et al 2020;Kotresha and Siddeshwari 2021). Several wild fruit trees, such as Spondias lutea L., are also used as nesting sites for different types of honey bees, which produce high-quality honey that is harvested and sold by local communities to improve their household income (Jasmi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Wild edible fruits have also been proven to enhance household food security under normal conditions (Broegaard et al 2017), as well as during crop insufficiency (Erskine et al 2015) in both rural and urban areas (Clark and Nicholas 2013). Moreover, the wild edible fruit plants have multiple uses such as cosmetics (Gebauer et al 2016), medicine (Tshikalange et al 2016;Dreher 2018;Elfrida et al 2021;Majumder et al 2021;Navia et al 2021a;Suwardi et al 2021), spices or condiments (Navia et al 2020a), crafts (Atato et al 2012;Hazarika and Singh 2018), traditional ceremonies (Sutrisno et al 2020), fiber (Karun et al 2014), fuel (Debela et al 2012;Klimas et al 2012), and even as a substantial income for local communities, particularly those living in remote areas (Deb et al 2013;Suwardi et al 2020;Kotresha and Siddeshwari 2021). Several wild fruit trees, such as Spondias lutea L., are also used as nesting sites for different types of honey bees, which produce high-quality honey that is harvested and sold by local communities to improve their household income (Jasmi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The ten articles were ( Rigat et al, 2009 ; Dansi et al, 2012 ; Donno et al, 2015 ; Bhartiya et al, 2015 ; Campanaro et al, 2019 ; Deb et al, 2019 ; Lambein et al, 2019 ; Donno and Turrini, 2020 ; Kumari and Chaudhary, 2020 ; Udeh et al, 2020 )…”
Section: Methodsmentioning
confidence: 99%
“…The ten articles were (Rigat et al, 2009;Dansi et al, 2012;Donno et al, 2015;Bhartiya et al, 2015;Campanaro et al, 2019;Deb et al, 2019;Lambein et al, 2019;Donno and Turrini, 2020;Kumari and Chaudhary, 2020;Udeh et al, 2020) The second stage: a systematic review We reviewed the ten articles, and a total of 34 terms (Table 1) were identified for use as keywords. From the review of the ten articles, it was observed that, in many instances, research articles on NUS often insinuate nutraceutical and pharmaceutical benefits without specifically mentioning the actual attribute(s).…”
Section: Identifying Abstractmentioning
confidence: 99%
“…The pressure of a rapidly growing population and the depletion of natural resources faster in developing countries has made it imperative to think about alternate food sources for human beings. There is a dire need to diversify present-day crops with different substitute products to fulfill basic human needs for food and diet [4]. The modification of farming practices has now shed light on many plants that have been recognized, but their consumption as food has not yet been in common practice.…”
Section: Introductionmentioning
confidence: 99%